Can psychopathic traits be adaptive? : Sex differences in relations between psychopathy and emotional distress - Međedović, Janko (Array, 2018)
One of the most prominent models of psychopathy operationalizes this construct as consisting of four factors: interpersonal, affective, lifestyle and antisocial traits. These traits show different relationship patterns with other constructs, and these relations may differ in men and women. The aim of this study was to investigate whether the relations between psychopathic traits and indicators of emotional distress (depression, anxiety and stress), differ between men and women. Data was collected on 650 students (60% women) at the University of Zagreb. The results of Canonical Correlation Analysis indicated that affective psychopathic traits have adaptive potential and represent a protective factor for experiencing emotional distress, while Lifestyle and Antisocial behavior represent risk factors for emotional distress. Moreover, sex had a moderating role in the relationship between Interpersonal and Lifestyle traits and distress, indicating that psychopathic traits seem to be more adaptive in males, compared to females.